Founders’ approach on successor selection: Game theory analysis - Jayantilal, Shital (2017)
Family firms are vital in economies worldwide. However, only a small minority of these outlive their founders. The founder’s lack of a proactive approach towards the succession process has been pointed out as a key contributor to that reality. This paper employs game theory to study the impact of the founder’s approach on successor selection in family firms. The results obtained for a founder who adopts an activist approach and invites his preferred successor are compared to those where the founder just reacts to his children initiating the succession race. The findings provide analytical evidence of the importance of the founder being proactive to safeguard intergenerational continuity as well as increase the propensity of his/her preferred successor being appointed.